Women's rituals and ceremonies in Shiite Iran and Muslim communities : methodological and theoretical challenges. - Khosronejad, Pedram (Iranian studies, 2015)
In this volume the authors present and discuss different aspects of their field research and experience in regard to women's rituals and devotional practices. One of the main aims of this book is to broaden our understanding of women's devotional lives, as well as calling attention to its relation to general social change. Most of the contributions are based on field research, direct observation and participation in rituals. This gives the reader a unique opportunity to better understand methodological challenges related to gender issues and field research among Muslim communities -- Présentation de l'éditeur.